الحاجات المعرفية ومصادر المعلومات لمريضات سرطان الثدي الخاضعات للمعالجة الكيماوية - غزال, سوسن; زحلوق, نديم; نعمان, مفيدة (Latakia University Journal -Medical Sciences Series, 2014)
مقدمة: يحتاج مريض السرطان للمعلومات ليس لمساعدته على فهم المرض ومعالجته فقط بل للسماح له بفهم التغيرات السلبية التي تحدث له خلال سير المرض مما يجعل التشخيص والمعالجة أقل إزعاجاً له. الهدف: طبق البحث الحالي لتحديد الحاجات المعرفية ومصادر المعلومات لمريضات سرطان الثدي الخاضعات للمعالجة الكيماوية. المناهج: قامت 60 مريضة بملء استبيان الحاجات المعرفية المكون من 47 سؤالاً حول الحاجات المعرفية وأضيف له الجزء الخاص بمصدر المعلومات مع تحديد الخيارات من ضمن الأفراد، والكادر الصحي، والمواد المطبوعة، والإعلام .النتائج:سجلت أغلب مريضات سرطان الثدي مستوىً عالياً من الحاجات المعرفية خلال فترة المعالجة الكيماوية. كما تمحورت الحاجات الأكثر أولوية حول الجزء الخاص بتطور المرض والمعالجة مع التركيز على البنود الخاصة باحتمالية انتشار السرطان، وفرص الشفاء، والتأثيرات الجانبية للمعالجة الكيماوية وكيفية تدبيرها بالإضافة إلى المعرفة حول احتمالية ظهور السرطان لدى أفراد الأسرة المقربين مثل الابنة أو الأخت. كما أظهر البحث اعتماد المريضات على الأطباء والمرضى الآخرين والتلفاز كمصدر للمعلومة أكثر بكثير من اعتمادهن على الممرض والانترنت. الاستنتاجات:نستنتج من البحث الحاجة لبرامج تثقيفية تلبي حاجات المريضة المعرفية بالإضافة إلى ضرورة تفعيل الدور التثقيفي للممرض بحيث تصبح الرعاية التمريضية المقدمة لمريضة سرطان الثدي شاملة لكل الجوانب الصحية لديها. Background: A cancer patient demands information, not only to assist him to understand the disease and its treatment, but also to allow him to interpret the negative events and action taken, through the course of disease, so that the threat inherent from the diagnosis and treatment becomes lessened. Methods: With the goal of studying the information needs and source of information of women with breast cancer who were receiving chemotherapy, 60 patients were invited to complete a self-administered questionnaire which consists of 47 item about information needs and 3 questions about sources of information with three choices (personnel, printed materials and mass media). They fill it at the early stage of their chemotherapy treatment. Results :The results showed that the majority of patients reported high level of information needs. Cancer and its spread, treatment, and side effects of chemotherapy as well as its management were priority information needs, in addition to the possibility of cancer occurrence among sisters and daughters. Results also demonstrated that the patients depended on doctors and other patients as sources of information more than on nurses and the internet. Conclusion: Findings indicate that there is a need for the provision of education program that addresses patients' information needs. Moreover, there is a necessity for ascertaining the role of educational nursing in affording holistic nursing care for breast cancer patients.